Long working hours and health status among employees in Europe: between-country differences - Lucía Artazcoz; Imma Cortès; Vicenta Escribà-Agüir; Xavier Bartoll; Helena Basart; Carme Borrell (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: This study aimed to (i) identify family responsibilities associated with moderately long working hours (41-60 hours a week); (ii) examine the relationship between moderately long working hours and three health outcomes; and (iii) analyze whether patterns differ by welfare state regimes. METHODS: The sample was composed of all employees aged 16-64 years working 30-60 hours a week interviewed in the 2005 European Working Conditions Survey (9288 men and 6295 women). We fitted multiple logistic regression models separated by sex and welfare state regime typologies. RESULTS: Married males were more likely to work long hours in countries with male breadwinner models whereas family responsibilities were related to long working hours among both sexes in countries with dual breadwinner models. The association between long working hours and health was (i) stronger among men in countries with male breadwinner models, primarily in Anglo-Saxon countries [adjusted odds ratio (OR_adj) associated with working 51-60 hours of 6.43, 6.04 and 9.60 for work-related poor health status, stress and psychological distress, respectively); (ii) similar among both sexes in Nordic countries; and (iii) stronger among women in Eastern European countries. CONCLUSIONS: In the European Union of 25 members (EU-25), working moderately long hours is associated with poor health outcomes with different patterns depending on welfare state regimes. The findings from this study suggest that the family responsibilities and breadwinner models can help explain the relationship between long working hours and health status.